Amnioinfusion in very early preterm prelabor rupture of membranes (AMIPROM): pregnancy, neonatal and maternal outcomes in a randomized controlled pilot study. (May 2014) - Roberts, D.; Vause, S.; Martin, W.; Green, P.; Walkinshaw, S.; Bricker, L.; Beardsmore, C.; Shaw, N.; McKay, A.; Skotny, G.; Williamson, P.; Alfirevic, Z.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2014; 43: 488–488